STUDIES ON DEMERSAL FISHES OF THE DEEP NERITIC WATERS AND THE CONTINENTAL SLOPE I. On the Stromateoid Fish Psenes indicus (Day) from the Indian Seas, wifli Comments on the Genus and Related Species and Notes on Its Biology - Silas, E G; Prasad, N K (Indian Journal of Fisheries, 2011)
IN the course of the last seven years the senior author has been able to make collections of pelagic and bathypelagic fishes as well as neritic deep-water fishes found more abundantly towards the edge of the continental shelf, from off the south-west coast of India during cruises of the Research Vessel VARUNA and other vessels operating in association with it. These investigations, which are in progress, were taken up primarily for getting a more complete picture of the ichthyofauna of the area to enable proper identifications and studies of the fish eggs and larvae of the plankton collected during these cruises. Diverse gear, namely, otter trawls, Isaacs-Kidd midwater trawls, longlines, driftnets, handlines and plankton ringnets of different sizes have been used for making the collections.